2012
DOI: 10.1007/s12012-012-9180-0
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Trichloroethylene Alters Cytochrome P450-2C Subfamily Expression in the Developing Chick Heart

Abstract: Trichloroethylene (TCE) is an organic solvent and common environmental contaminant. TCE exposure is associated with heart defects in humans and animal models. Primary metabolism of TCE in adult rodent models is by specific hepatic cytochrome P450 enzymes (Lash et al., 2000). As association of TCE exposure with cardiac defects is in exposed embryos prior to normal liver development, we investigated metabolism of TCE in the early embryo. Developing chick embryos were dosed in ovo with environmentally relevant do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 35 publications
0
19
1
Order By: Relevance
“…If EETs really play a role in development, alterations in the strict spatio-temporal pattern of the expression of CYP epoxygenases and/or sEH during human prenatal development by xenobiotics could have adverse consequences for the developing organism. Recently, it has been described that changes in the expression of CYP2C induced by trichlorethylene cause improper development of the chicken heart [Makwana et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
“…If EETs really play a role in development, alterations in the strict spatio-temporal pattern of the expression of CYP epoxygenases and/or sEH during human prenatal development by xenobiotics could have adverse consequences for the developing organism. Recently, it has been described that changes in the expression of CYP2C induced by trichlorethylene cause improper development of the chicken heart [Makwana et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for chemical disruption of these processes is available for trichloroethylene (TCE), estrogens, dioxin, cigarette smoke, other volatiles such as alcohol and metals among other compounds. Amongst these chemicals, TCE, an organic solvent and common environmental contaminant, used primarily as an industrial degreasing agent as n-hexane, has been well studied on the association between exposure and congenital heart malformations [20,37,38]. Data has demonstrated that the earliest embryonic expression of phase I detoxification enzymes is in the developing heart, and expression of these CYPs is relevant to the susceptibility of the developing heart to environmental teratogens [37].…”
Section: Discussionmentioning
confidence: 99%
“…Amongst these chemicals, TCE, an organic solvent and common environmental contaminant, used primarily as an industrial degreasing agent as n-hexane, has been well studied on the association between exposure and congenital heart malformations [20,37,38]. Data has demonstrated that the earliest embryonic expression of phase I detoxification enzymes is in the developing heart, and expression of these CYPs is relevant to the susceptibility of the developing heart to environmental teratogens [37]. Any perturbation of cardiac function contributes to the etiology of congenital heart defects in TCEexposed embryos, while the ventricular septal defect induced by TCE may be secondary to functional impairments that alter cardiac hemodynamics and subsequent ventricular foramen closure, which is consistent with recent demonstrations that TCE impairs calcium handling in cardiomyocytes [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…However, CYP epoxygenases are up-regulated by PPARa in human beings, and their spatio-temporal expression pattern in human embryonic/ foetal tissues has been described recently [16]. It has also been noted that changes in the expression of CYP2C induced by the environmental teratogen trichloroethylene lead to improper development of the chicken heart [17]. Trichloroethylene is a known PPARa ligand and whether this effect is mediated by this receptor warrants further investigation.…”
Section: Resultsmentioning
confidence: 99%